Pengaruh Pemberian Ekstrak Tauge (Vigna radiata (L)) terhadap Kadar Serum Trigliserida pada Tikus Wistar Jantan yang Diinduksi Kuning Telur (The Effect of Mungbean (Vigna radiata (L)) Sprout on Triglyceride Serum Levels of Male Wistar Rats Induced by Eg - Fairuztya Naila Maris; Rena Normasari; Rini Riyanti (Pustaka Kesehatan, 2016)
Dyslipidemia is a condition of abnormal blood lipid profiles, including hypertriglyceridemia. One of antidislipidemia agent is niasin, that can be found in mungbean (Vigna radiata (L)) sprout. This study aimed to determine the difference in triglyceride serum after treatment with mungbean sprout extract on male wistar rats induced by egg yolk. This was an experimental study with randomized Post-test Only Control Group Design. Twenty five male wistar rats aged 2-3 months, divided into 5 groups: K(-), K(+), P1, P2 and P3. K(-) was treated with standard diet. The other four groups were injected with 0,006 mg/ 200 gram weight IV adrenalin on the first day followed by egg yolk diet for six weeks. P1, P2, and P3 group were treated with 50, 100, and 200 mg/ 200 g/day of mungbean sprout extract simultaneously with the diet. At the end of the treatment, the serum was taken to examine the triglyceride serum. Average levels of triglycerides serum in group K(-) 69,2±15,9; K(+) 92±14,9; P1 63,2±14,1; P2 53±6,9; P3 84,8±23,9. There was significant different of triglyceride serum means between group K(+) and P2 (p=0,014). In conclusion, 100 mg of mungbean sprout extract showed a significant difference in triglyceride serum with control group of male wistar rats induced with egg yolk.   Keywords: Mungbean sprout, egg yolk, triglyceride